Caffeine affects CD8+ lymphocyte apoptosis and migration differently in naïve and familiar individuals following moderate intensity exercise. (June 2016) - Navalta, James W; Fedor, Elizabeth A; Schafer, Mark A; Lyons, T Scott; Tibana, Ramires A; Pereira, Guilherme B; Prestes, Jonato
The purpose of this investigation was to determine the lymphocyte subset response to 30 min of moderate treadmill exercise during caffeine supplemented (6.0 mg.kg −1 ) and placebo conditions in caffeine-naïve and -familiar individuals. Seventeen individuals participated (caffeine-familiar = 8, caffeine-naïve = 9) completing two exercise bouts (caffeine supplemented and placebo control) 48 h apart in a counterbalanced and double-blinded fashion. Individuals were classified as follows: caffeine-naive <50 mg.d −1 and caffeine-familiar >200 mg.d −1 . Whole blood samples were obtained at rest, 30 min after caffeine or placebo ingestion, immediately following exercise, and 1 h post exercise. Blood was used to analyze apoptosis (annexin V) and cellular migration (CX3 CR1) responses in lymphocyte subsets (CD4+, CD8+, CD19+). Absolute changes from rest values were calculated and differences between conditions were determined through Chi-squared analysis with significance accepted at P <0.05. With regard to CD4+ and CD19+ lymphocytes, the interaction of caffeine and exercise did not affect naïve individuals to a greater extent immediately post exercise when compared to familiar, as similar apoptotic and migratory responses were observed ( P >0.05). However, CD8+ lymphocyte cell death and migration responses were observed to be significantly greater at each sampling point in caffeine-familiar individuals ( P <0.05). It is possible that chronic caffeine supplementation may prime CD8+ cell receptors for responsiveness to apoptosis and migration and the consequence of this form of immunosuppression in the post-exercise period should be determined.